2018
DOI: 10.1111/desc.12667
|View full text |Cite
|
Sign up to set email alerts
|

Infants' visual sustained attention is higher during joint play than solo play: is this due to increased endogenous attention control or exogenous stimulus capture?

Abstract: Previous research has suggested that when a social partner, such as a parent, pays attention to an object, this increases the attention that infants pay to that object during spontaneous, naturalistic play. There are two contrasting reasons why this might be: first, social context may influence increases in infants' endogenous (voluntary) attention control; second, social settings may offer increased opportunities for exogenous attentional capture. To differentiate these possibilities, we compared 12-month-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 60 publications
(134 reference statements)
10
76
0
1
Order By: Relevance
“…Particularly of interest was Figure 3c, which suggested that negative-lag relationships (attention forward-predicting EEG power) were similar across the Solo and Joint Play conditions, but that positive-lag relationships (EEG power forward-predicting attention) were present only during Solo Play. These results are consistent with our previous research suggesting that endogenous factors, such as attentional inertia, influence infants' attention more during solo (non-interactive) play than during joint play ( [25]). Taken together, our results suggest that infants' endogenous neural control over attention is greater during solo play.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Particularly of interest was Figure 3c, which suggested that negative-lag relationships (attention forward-predicting EEG power) were similar across the Solo and Joint Play conditions, but that positive-lag relationships (EEG power forward-predicting attention) were present only during Solo Play. These results are consistent with our previous research suggesting that endogenous factors, such as attentional inertia, influence infants' attention more during solo (non-interactive) play than during joint play ( [25]). Taken together, our results suggest that infants' endogenous neural control over attention is greater during solo play.…”
Section: Discussionsupporting
confidence: 93%
“…A previous report based on these data, that contained behavioural findings only, reported that infants showed longer look durations towards the object during Joint Play (JP) relative to Solo Play (SP), together with shorter periods of inattention (see Supplementary Figure S1) ( [25]). Supplementary Figure S2 compares EEG power for infants and parents between Solo Play and Joint Play; no significant between-condition differences were observed.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations